Heat stress suppresses DNA replication and mitosis in barley root apical meristems - Kaduchová, Kateřina; Šály, Peter; Kashkan, Ivan; Pecinka, Ales (Frontiers in Plant Science, 2025)
Increasing temperature affects plant development, with the assumption that roots are among the tissues particularly sensitive to heat stress (HS). However, a comprehensive analysis of the impact of high temperature on the dynamics of cell cycle and mitosis in barley root cells remains limited. Here, we analyzed barley root growth across a temperature gradient from 15°C to 37°C, encompassing ambient, thermomorphogenic, and HS conditions. Root growth was stimulated by moderately elevated temperatures but arrested at approximately 35°C. HS-changed nuclear architecture parameters, including expanded nuclear area and altered circularity. Although HS led to a temporary mitosis arrest, we demonstrated that DNA replication and mitotic activity were efficiently reinitiated upon recovery at a lower temperature. Finally, we showed that moderately higher temperatures speed up mitosis. Notably, anaphase was the least affected compared to other mitotic phases. In summary, we show that germinating barley plantlets sustain active growth at high speed to temperatures above 30°C and that HS blocks cell cycle around the two critical cell cycle stages – S phase and mitosis in barley. These observations expand the knowledge of barley root growth under high temperatures and will help develop HS-resilient cereals.